Organic Vs Inorganic Growth: A Case Study - Jacob, Miriam (2006)
In today's dynamic and competitive business environment, growth is not just an option for companies, it is a vital necessity. No longer is it enough to generate reasonable amount of profits.Companies now factor in expansion on a large scale in their corporate vision almost from their very inception. Taking the need for expansion as a given, the next question that business organizations face is the mode of expansion to adopt. The different methods by which companies can grow can broadly be classified under two heads-organic growth and inorganic growth. This dissertation addresses these issues in the context of the Indian IT Sector. After reviewing the theoretical background pertaining to both Organic and Inorganic (Mergers and Acquisitions) growth, discussing some of the pros and cons of both methods I try to find out, which is in fact, a better business strategy to pursue. An extensive review of the literature on the financial performance indicators of organic and inorganic growth will also be undertaken. Given the paucity of research on organic growth per se, I will be focusing on selected case studies (pertaining to software and product development industry in the Indian IT Sector) to further explain which is a "better alternative". Prior literature on both Organic and Inorganic has shown varied results. In this research, the results from both the accounting studies as well as the independent sample t-test show that no significant benefit accrues from taking up one form over the other.